La importancia del pensamiento sistémico para el aprendizaje del concepto de red trófica en educación básica primaria y secundaria (Memorias Sifored - Encuentros Educación UAN, 2021)
This article presents a systematic review on the learning of food chain from systemic thinking in basic primary and secondary education. From the search in the Science Direct, Scopus, and Nature databases, the academic Google and Researchgate search engines and the repositories of the Luis Ángel Arango Library and three universities from Bogotá (Antonio Nariño, Pedagógica y Javeriana), 51 specialized documents are analyzed that allow establishing that the Research on systemic thinking applied to food web learning is very limited, despite its positive impact on the development of cognitive abilities in students, by promoting complex thought structures with relevance in the interrelational, multicausal and multidirectional aspects. It also establishes that a progressive construction of the concept of food chain from systemic thinking with the help of the so-called transition hypotheses allows overcoming difficulties in learning by favoring the construction of a conceptual structure with different levels, contents and categories.
Keywords: Natural sciences; food chains; systemic thinking; school ecology